Epigenetically programmed identity crisis to combat diffuse large B cell lymphoma - Niccolai, Rachele; Göbel, Camiel; Jacobs, Heinz (Trends in immunology, 2025)
A substantial fraction of patients with diffuse large B cell lymphoma (DLBCL) does not respond to standard-of-care immunochemotherapy.B cell differentiation is intimately associated with defined changes of the epigenetic landscape.DLBCL relies on epigenetic regulators to preserve their proproliferative and differentiation-arrested cell identity.Targeting epigenetic regulators has proved effective in unlocking the differentiation arrest of normal as well as malignant B cells. Transcriptional and epigenetic dysregulations during B cell differentiation can lead to diffuse large B cell lymphoma development by locking cells in a proliferative and antiapoptotic state. Understanding how these regulators sustain tumor cell identity is essential for new therapeutic strategies. This review introduces the epigenetically programmed identity crisis strategy, which leverages epigenetic drugs to destabilize tumor cell identity and forces them into nonviable states. A comprehensive understanding of normal germinal center B cell differentiation is essential for deciphering the mechanisms underlying malignant transformation. Germinal center B cell–like diffuse large B cell lymphoma (GCB-DLBCL) originates from the malignant transformation of germinal center B cells. This process is driven by transcriptional and epigenetic dysregulations, frequently caused by recurrent mutations and chromosomal translocations. These changes lead to a differentiation arrest associated with unchecked proliferation and survival. This review highlights key transcriptional and epigenetic dependencies that sustain the GCB-DLBCL phenotype and identifies therapeutic vulnerabilities. Epigenetic targeting of these vulnerabilities unlocks tumor cells from their differentiation arrest, enabling further yet incomplete differentiation toward an antiproliferative, proapoptotic plasma cell–like or memory B cell–like state. We define this transition as an epigenetically programmed identity crisis, a promising therapeutic strategy to target GCB-DLBCL and potentially other malignancies. Germinal center B cell–like diffuse large B cell lymphoma (GCB-DLBCL) originates from the malignant transformation of germinal center B cells. This process is driven by transcriptional and epigenetic dysregulations, frequently caused by recurrent mutations and chromosomal translocations. These changes lead to a differentiation arrest associated with unchecked proliferation and survival. This review highlights key transcriptional and epigenetic dependencies that sustain the GCB-DLBCL phenotype and identifies therapeutic vulnerabilities. Epigenetic targeting of these vulnerabilities unlocks tumor cells from their differentiation arrest, enabling further yet incomplete differentiation toward an antiproliferative, proapoptotic plasma cell–like or memory B cell–like state. We define this transition as an epigenetically programmed identity crisis, a promising therapeutic strategy to target GCB-DLBCL and potentially other malignancies.